STRUCTURAL AND FUNCTIONAL ENAMEL RESISTANCE (TER-TEST) IN CHILDREN WHO ARE STUDYING IN BOARDING SCHOOL - О. Narepekha; Т. Lisak (Ukrainian Medical Stomatological Academy, 2015)
The survey of children of boarding schools and orphanages has indicated a high prevalence of dental caries in all age groups. The intensity of caries in these children is much higher compared with children of secondary schools. The significant role in the development of dental caries in these children is played by complex factors, including the reduced resistance of dental hard tissues. Therefore, assessment of resistance of enamel is important in terms of the development of preventive measures in children of boarding schools. The aim of the study. To estimate the structural and functional resistance of enamel in children of boarding schools. Materials and methods. To study the structural and functional enamel resistance we performed dental examination and determination TER test in 155 children from boarding schools (study group) and 127 children from the secondary school (comparison group) aged 7, 12 and 15 years. To assess dental caries lesion prevalence (in %) and intensity index DMF were recorded. TER-test was determined by Okushko, Kosarev. The results were statistically processed using Student's t test. The results indicate that the structural and functional resistance of enamel in children from boarding schools is, on average, 4,96 ± 0,36 points, and meets the criteria of the lowered resistance of enamel, which is significantly higher in comparison with the group of children (3,43 ± 0,25 points (p<0,01), corresponding criterion as caries-resistant enamel. Significantly higher levels of TER-test were found in all age groups of children from boarding schools. More pronounced TER-test difference was found between children of 12 years who are in boarding schools and their peers from secondary schools (4,83 ± 0,29 points and 3,14 ± 0,24 points, respectively, p<0,001). Analysis by age shows the increasing structural and functional resistance of enamel in children in the main and control group. However, it should be noted that in structural and functional resistance of enamel is reduced in children at the age of 7 years from orphanages (6,06 ± 0,41 points) and is increased to 4,01 ± 0,16 points (p<0,05) in children at the age of 15 years. In children from secondary schools conditionally resistant enamel was found only in children at the age of 7 years and at the age of 15 it was increased to 2,78 ± 0,21 points, corresponding to the high resistance of enamel. Thus, evaluation of structural and functional resistance of enamel in children from boarding schools suggests much lower resistance of enamel compared with children from secondary schools. In children from orphanages structural and functional enamel resistance meets the criteria of low resistance, and in the children from secondary school meets the criteria of caries-resistant enamel. When multiple dental caries is in children of orphanages, enamel meets the criteria of caries susceptible, and the children of secondary school - conditionally resistant. It has been proved that the most intensive processes of maturation of enamel occur at the age from 7 to 12 years. The results encourage the use of differentiated prevention that enhances the resistance of enamel in children of orphanages.